2020
DOI: 10.1080/09645292.2020.1822787
|View full text |Cite
|
Sign up to set email alerts
|

ICT Use at home for school-related tasks: what is the effect on a student’s achievement? Empirical evidence from OECD PISA data

Abstract: In this paper, we have employed data from the OECD's Programme for International Student Assessment (PISA, 2012 edition) on the EU-15 countries in order to investigate the relationship between (i) the way in which students use ICT at home for school-related purposes and (ii) their test scores in reading, mathematics and science. By employing two different econometric techniquesnamely, propensity score matching and instrumental variableswe can provide evidence that in most countries there is an association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 40 publications
1
22
0
5
Order By: Relevance
“…While reviewing the literature, it was noticed that the early studies leading to this scale originated from the ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ use of ICT in school and in home (Meng et al, 2019). Researchers obtained mixed results about the effect of using computer and technology on students' success (Agasisti et al, 2020;Chen & Wang, 2013;Eickelmann et al, 2016;Lei & Zhao, 2007;Liemb et al,2014;Notten & Kraaykamp, 2009;Thiessen & Looker, 2007;Xin & Zhou, 2010). For example, Thiessen and Looker (2007) showed that intensive computer use in Canada was negative relationship with students' reading performance whereas Xin and Zhou (2010) showed that computer technology use increased students' performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While reviewing the literature, it was noticed that the early studies leading to this scale originated from the ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ use of ICT in school and in home (Meng et al, 2019). Researchers obtained mixed results about the effect of using computer and technology on students' success (Agasisti et al, 2020;Chen & Wang, 2013;Eickelmann et al, 2016;Lei & Zhao, 2007;Liemb et al,2014;Notten & Kraaykamp, 2009;Thiessen & Looker, 2007;Xin & Zhou, 2010). For example, Thiessen and Looker (2007) showed that intensive computer use in Canada was negative relationship with students' reading performance whereas Xin and Zhou (2010) showed that computer technology use increased students' performance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Thiessen and Looker (2007) showed that intensive computer use in Canada was negative relationship with students' reading performance whereas Xin and Zhou (2010) showed that computer technology use increased students' performance. Using PISA 2012 data from 15 European countries, the study showed that intensive computer use in homework negatively affected test scores in all areas (Agasisti et al, 2020). It could be argued that the first studies about ICT in the literature were about the effect of computer or internet use on success in school and in home (Meng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Κάποιος µπορεί, για παράδειγµα, να καταλήξει σε µια µετασχηµατιστική άποψη, παρατηρώντας ότι η τεχνολογία µετασχηµατίζει τη φύση της εκπαίδευσης (Reinking & Kieffer, 2019). Από την άποψη αυτή, στόχος της έρευνας µπορεί να αποτελέσει η κατανόηση των νέων µορφών γραµµατισµού λόγω των ΤΠΕ και το πώς τα πολυµέσα, το ηλεκτρονικό ταχυδροµείο και άλλες τεχνολογίες µετασχηµατίζουν τον Ψηφιακό Γραµµατισµό και την µάθηση τους στην τάξη, στο σπίτι ή σε άλλους κοινωνικούς χώρους (Agasisti et al, 2017• Attewell & Battle, 1999•Bulman & Fairlie, 2016• Fraillon et al, 2014c• van Deursen & van Diepen, 2013• Vekiri & Chronaki, 2008. Μια τέτοια προσέγγιση παρέχει σηµαντικές γνώσεις σχετικά µε τις πολλές αλλαγές που συντελούνται στη φύση του Ψηφιακού Γραµµατισµού αλλά και της µάθησης µε την χρήση των ΤΠΕ γενικότερα.…”
Section: η σύνθεση των επιµέρους εννοιώνunclassified
“…Τις τελευταίες δεκαετίες, οι έννοιες της ψηφιακής ικανότητας και του Ψηφιακού Γραµµατισµού έχουν χρησιµοποιηθεί και αποτελούν µέρος ενός ευρύτερου δηµοσίου διαλόγου που σχετίζεται µε την εκπαιδευτική πολιτική στο πλαίσιο διερεύνησης: α) σχετικά µε τι είδους δεξιότητες και γνώσεις πρέπει να έχουν οι µαθητές σε µια κοινωνία της γνώσης, και β) σε ποιο βαθµό πρέπει να εφαρµοστούν οι υπάρχουσες διαστάσεις του Ψηφιακού Γραµµατισµού στις νέες συνθήκες που διαµορφώνονται (Jimoyiannis & Gravani, 2010• Ferrari et al, 2013a• Ilomäki et al, 2016b• Powell, 2017 (Agasisti et al, 2017•Fraillon et al, 2014c. Στο περιβάλλον του σπιτιού, η χρήση των ΤΠΕ από τους µαθητές επηρεάζει την επίδοσή τους και σε άλλα γνωστικά αντικείµενα (Attewell & Battle, 1999•Naevdal, 2007•Wittwer & Senkbeil, 2008.…”
Section: εκπαιδευτικές πολιτικές για τον ψηφιακό γραµµατισµόunclassified
See 1 more Smart Citation